CONTRIBUTION OF THE CYTOLOGY OF PAPANICOLAOU FOR THE DIAGNOSIS OF YEASTS IN VAGINAL SECRETION - Carneiro, Soraia S.; Peralta, Rosane M.; Svidzinski, Terezinha I. E.; Consolaro, Marcia E. L. (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction: vulvovaginal Candidiasis vulvovaginal (VVC) it is an infection caused by the abnormal growth of fungus of the type yeasts in the mucous membrane of the genital treatment. Lately, it has been increasing the interest in the use of the cytology of Papanicolaou (Pap) in the diagnosis of associated infections the pathogens of sexual transmission, but the method has been little appraised for VVC. Objectives: to evaluate the accuracy diagnostic of the cytology of Papanicolaou for the diagnosis of vaginal fungus, as well as to compare the results of the cytology with the one of the bacterioscopy of vaginal secretion (Gram) and culture. Methods: cervico-vaginal secretions were collected for Gram, Papanicolaou and culture of yeasts, and the grown colonies in the culture were counted. The women didn’t go selected to simptomatology of VVC and they were discarded those with other infection agent or immunodeficiency. Statistical calculations of sensibility were accomplished, specificity, values positive and negative predictive, and frequency of false positive and negative, in three situations: in the independent detection of fungus of the amount of colonies; in the cases with growth of 1-9 colonies; and in those with growth of ≥ 100. Results: the culture of it was positive in 35 patients (21,70%). Without considering the number of colonies, the sensibility of Gram and of the cytology they were very similar (67,65% and 62,85%), in the cases with growth of 1-9 colonies, of 37,50% and 50,00%, and in the cases with growth ≥ 100 colonies, of 86,61% and 78,26%. Conclusion: the cytology was shown a morphologic method with very similar efficiency and for small numbers of colonies better than Gram to detect vaginal yeasts, turning her perfectly applicable in the routine laboratorial for this diagnosis